Ki67 expression in invasive breast cancer: the use of tissue microarrays compared with whole tissue sections - Muftah, Abir A.; Aleskandarany, Mohammed A.; Al-kaabi, Methaq M.; Sonbul, Sultan N.; Diez-Rodriguez, Maria; Nolan, Christopher C.; Caldas, Carlos; Ellis, Ian O.; Rakha, Emad A.; Green, Andrew R. (Springer, 2017)
Background: Although the prognostic value of Ki67 in breast cancer is well documented, using optimal cut-points for patient stratification, reproducibility of the scoring and interpretation of the results remain a matter of debate particularly when using Tissue Microarrays (TMAs). This study aims to assess Ki67 expression assessed on TMAs and their matched whole tissue sections (WTS). Moreover, whether the cut-off used for WTS is reproducible on TMA in BC molecular classes and the association between Ki67 expression cut-off, assessed on TMAs and WTS, and clinicopathological parameters and patient outcome will also be tested. Method: A large series (n=707) of primary invasive breast tumours were immunostained for Ki67 using both TMA and WTS and assessed as percentage staining and correlated with each other, clinicopathological parameters and patient outcome. In addition, MKI67 mRNA expression was correlated with Ki67 protein levels on WTS and TMAs in a subset of cases included in the METABRIC study. Results: There was moderate concordance in Ki67 expression between WTS and TMA when analysed as a continuous variable (Intraclass correlation coefficient=0.61) and low concordance when dichotomised (kappa-value=0.3). TMA showed low levels of Ki67 with mean percentage of expression 35% 22% on WTS and TMA, respectively. MKI67 mRNA expression was significantly correlated with protein expression determined on WTS (Spearman Correlation, r=0.52) and to a lesser extent on TMA (r=0.34) (p<0.001). Regarding prediction of patient outcome, statistically significant differences were detected upon stratification of patients with tumours expressing Ki67 at 10%, 15%, 20%, 25% or 30% in TMA. Using TMA, ≥20 % Ki67 provided the best prognostic cut-off particularly in triple negative and HER2 positive classes. Conclusion: Ki67 expression in breast cancer can be evaluated using TMA although different cutpoints are required to emulate results from WTS. A cut-off of ≥ 20 % for Ki67 expression in BC provides the best prognostic correlations when TMAs are used.